2010
DOI: 10.1007/s00122-010-1337-2
|View full text |Cite
|
Sign up to set email alerts
|

Pyramided QTL underlying tolerance to Phytophthora root rot in mega-environments from soybean cultivars ‘Conrad’ and ‘Hefeng 25’

Abstract: Phytophthora root rot (PRR) of soybean (Glycine max (L.) Merr.) is the second most important cause of yield loss by disease in North America, surpassed only by soybean cyst nematode (Wrather et al. in Can J Plant Pathol 23:115-121, 2001). Tolerance can provide economically useful disease control, conditioning partial resistance of soybean to PRR. The aims of this study were to identify new quantitative trait loci (QTL) underlying tolerance to PRR, and to evaluate the effects of pyramided or stacked loci on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 36 publications
5
70
1
1
Order By: Relevance
“…As mentioned earlier, Conrad and AC Colombe are also favored for their increased resistance to P. sojae (Poysa, personal communication) and other soybean pathogens [28, 29]. Therefore, the differential expression of genes involved in stress response, localized to the root hairs could be suggestive of a mechanism underlying the improved resistance to pathogen infection.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As mentioned earlier, Conrad and AC Colombe are also favored for their increased resistance to P. sojae (Poysa, personal communication) and other soybean pathogens [28, 29]. Therefore, the differential expression of genes involved in stress response, localized to the root hairs could be suggestive of a mechanism underlying the improved resistance to pathogen infection.…”
Section: Discussionmentioning
confidence: 94%
“…Four soybean cultivars were chosen for this study: two with increased resistance to stem and root rot disease caused by Phytophthora sojae , Conrad and AC Colombe; two with susceptibility to P. sojae , AC Glengarry and Pagoda (Poysa, personal communication). Multiple sources have cited increased resistance in Conrad soybeans to a broad range of pathogen infection ( Fusarium graminearum and P. sojae ) [28, 29]. …”
Section: Introductionmentioning
confidence: 99%
“…The cumulative effects of QTL pyramiding have been proved previously in soybean (Li et al 2010;Njiti et al 2001Njiti et al , 2002) and other crops (Huang et al 1997;Jiang et al 2007;Richardson et al 2006). In this study, we analyzed the cumulative effects of QTL for the saturated fatty acids by a group comparison of different QTL combinations for multiple loci based on the results of ANOVA (Jiang et al 2007).…”
Section: Two-locus Combinationmentioning
confidence: 97%
“…The cumulative effects of QTL pyramiding have been proven previously in soybean (Li et al 2010;Njiti et al 2001Njiti et al , 2002 and in other crops (Huang et al 1997;Jiang et al 2007;Richardson et al 2006). Li et al (2010) analyzed Phytophthora root rot tolerance in a RIL population and evaluated the cumulative effects of the detected QTL. Their results indicated that the plant tolerance to Phytophthora root rot was correlated with the number of loci carrying resistance alleles.…”
Section: Comparison Of Qtls Detected In Different Studiesmentioning
confidence: 97%